Effects of Perceived Fairness and Tariff Changes Against Compliance of Taxpayer Post PP No. 23 of 2018 - Prastyatini, Sri Lestari Yuli; Fitria, Lussi (IJMA (Indonesian Journal of Management and Accounting), 2022)
Tax collection is mandatory and transferred from the wealth of the community to the state, this is so as not to cause obstacles and resistance to tax collection which must meet the requirements of justice so that taxpayers feel fair in implementation and fair in legislation. In addition, the government is anticipating efforts to maximize revenue from the tax sector by issuing PP No. 23 of 2018 where there is a change in the final PPh rate from 1% to 0.5%. This study aims to examine the effect of perceptions of fairness and changes in tariffs on taxpayer compliance after the stipulation of PP No. 23 of 2018. The population of this study is all MSME taxpayers in Lamandau district with purposive sampling. The method used in this study is a quantitative method using primary data from a questionnaire. The results of this study indicate that perceptions of fairness and changes in tariffs have an effect on taxpayer compliance after the stipulation of government regulation number 23 of 2018